2013
DOI: 10.1038/srep02478
|View full text |Cite
|
Sign up to set email alerts
|

Differential lung NK cell responses in avian influenza virus infected chickens correlate with pathogenicity

Abstract: Infection of chickens with low pathogenicity avian influenza (LPAI) virus results in mild clinical signs while infection with highly pathogenic avian influenza (HPAI) viruses causes death of the birds within 36–48 hours. Since natural killer (NK) cells have been shown to play an important role in influenza-specific immunity, we hypothesise that NK cells are involved in this difference in pathogenicity. To investigate this, the role of chicken NK-cells in LPAI virus infection was studied. Next activation of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…Recently, we (21) reported diminished activation of lung NK cells upon infection with the highly pathogenic H5N1 virus in chickens. Additional studies are warranted to investigate whether the AIV-specific CHIR is involved in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we (21) reported diminished activation of lung NK cells upon infection with the highly pathogenic H5N1 virus in chickens. Additional studies are warranted to investigate whether the AIV-specific CHIR is involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…All cells were cultured at 37˚C, 5% CO 2. Primary lung cells were isolated from Lohmann Brown chickens infected with the LPAI virus strain H9N2 isolate A/chicken/United Arab Emirates/99 at 1 d postinfection, as previously described (21), and stored at 2140˚C until use. Chickens were housed, handled, and treated following approval by the Animal Experimental Committee of the Veterinary Faculty of Utrecht University, and the experiments were performed in accordance with the Dutch regulation on experimental animals.…”
Section: Cell Lines and Primary Cellsmentioning
confidence: 99%
“…The model was used to fit data from 44 experimentally influenza infected volunteers and predicted that NK cell levels peak around day 4 after infection and then decay slowly, whereas pro-inflammatory cytokines peak at 2.2 days after infection and have a short half-life of 9.1 hr [24]. These results were recently confirmed by experiments showing that NK cell activation peaks between 3 and 5 days after infection [79, 80]. Also, if one assumes that the level of activated NK cells rapidly reaches a steady state, then by a quasi-steady state assumption N is proportional to the inflammatory cytokine level, F .…”
Section: Modeling Hcv Viral Kineticsmentioning
confidence: 98%
“…Intestinal mast cell response following Trichinella spiralis infection is dependent on T cells [124] 1994 Adaptive immune responses to Leishmania infantum correlate with disease progression in dogs [125] Another virus that has been studied by several Dutch research groups is Influenza A. This work ranges from the cellular and molecular mechanisms that drive protective anti-viral immunity [16][17][18][19][20][21], to the development of human antibodies with broadly neutralizing capacity against the virus [22,23]. Investigation into the cellular anti-viral response encompassed the polyclonality of the responding T cell pool, the role of T cell co-stimulation and the formation of memory T cells, but also the involvement of innate immune cells their contribution to pathology [16,[18][19][20]24].…”
Section: Schistosomiasis Leads To Hyporesponsive T Cells [121] 2000mentioning
confidence: 99%
“…This work ranges from the cellular and molecular mechanisms that drive protective anti-viral immunity [16][17][18][19][20][21], to the development of human antibodies with broadly neutralizing capacity against the virus [22,23]. Investigation into the cellular anti-viral response encompassed the polyclonality of the responding T cell pool, the role of T cell co-stimulation and the formation of memory T cells, but also the involvement of innate immune cells their contribution to pathology [16,[18][19][20]24]. Moreover, it has been shown that the inhibitory receptor CD200R plays an important role in diminishing immune pathology during influenza [25,26].…”
Section: Schistosomiasis Leads To Hyporesponsive T Cells [121] 2000mentioning
confidence: 99%